The Influence of Religiosity and Product Quality on Purchase Decisions for Muslim Clothing in E-commerce in Makassar City - Akramunnas Akramunnas; Muhammad Nasri Katman; Nurul Inayah (PT. Publikasiku Academic Solution, 2022)
Backgrounds: The rapid and sophisticated development of information and communication technology has brought major changes in aspects of life. People can now do things more easily thanks to technological advances, including trade. Aim: This study aims to determine the effect of religiosity and product quality on purchasing decisions for seasonal clothing in e-commerce in the city of Makassar. Methods: This research uses quantitative research methods. The sampling technique used was purposive non-probability sampling using Hair's theory, so that the number of samples in this study was 160 samples. Sources of data in this study are primary data and secondary data with data collection methods through questionnaires, observation, and documentation. Findings: the results of the study show that partially the religiosity and product quality variables have a significant influence on the purchasing decision of Muslim clothing in e-commerce. Simultaneously the religiosity and product quality variables have a significant influence on the purchasing decision of Muslim fashion in e -commerce in Makassar city. Based on the results of the test for the coefficient of determination, it was found that religiosity and product quality can influence the decision to purchase Muslim clothing in e-commerce by 0.519 or 51.9%. Meanwhile, the remaining 0.481 or 48.1 % is influenced by other variables not proposed in this study